O trabalho das mulheres na rede de produtoras do Pajeú: cuidados e economia feminista em práticas de economia solidária - Silva, Mônica Vilaça da (2019)
This dissertation develops itself from the work experience of women, organized in productive groups on the Rede de Mulheres Produtoras do Pajeú, localized in the Sertão do Pajeú in Pernambuco, presenting a problematization of the values, moral and ethical in senses, mobilized by women in their work practices. In that way, this work searches to reflect about the experiences and transformation of the daily, based on the work organization and the learning organized by women. The transformation in here discussed shares changing in norms and values, of coexistence dynamics and management and of the directions of work realized by women. The methodological orientations that guided the developing of this research explored to communicate the fact that the experiences analysed, were made by women only, considering their work options and economical organization, beyond the different times of organization and composition of women work groups. Moving from those observations, we will discuss the operability of research moving from methods and tools that dialogue with references of feminist epistemology and popular education. To develop these reflections, three dimensions will be debated in this analyses, first being the approach of public politics and organizational answers from women in the Sertão do Pajeú, reflecting on the appearance of women working groups in response of federal, state and municipal public politics and non-governmental organizations developed in different time periods on their territory. A second dimension will address the comprehensions built by women about work, what activities they define and comprehend as work and the strategies and steps of production and administration of work collectively realized by groups. Lastly, will be discussed the private and collective learnings resulting from this research realized on productive groups and how these learnings also involve the elaboration of definitions about the political principles of the groups, as it occurs whit your definition for a popular feminism, and the definitions of organizational maturity by your daily experience as it occurs in your choice by the network organization.